2008
DOI: 10.1038/ismej.2008.69
|View full text |Cite
|
Sign up to set email alerts
|

The rational exploration of microbial diversity

Abstract: The exploration of the microbial world has been an exciting series of unanticipated discoveries despite being largely uninformed by rational estimates of the magnitude of task confronting us. However, in the long term, more structured surveys can be achieved by estimating the diversity of microbial communities and the effort required to describe them. The rates of recovery of new microbial taxa in very large samples suggest that many more taxa remain to be discovered in soils and the oceans. We apply a robust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
163
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(169 citation statements)
references
References 37 publications
(60 reference statements)
6
163
0
Order By: Relevance
“…At the 3% clustering level, each of the sediment samples contained twice as many observed OTUs (B4100) as did the water column sample (B1850 OTUs). Chao and ACE estimators tend to underestimate actual richness owing to their extrapolation from small sample sizes (Hong et al, 2006;Quince et al, 2008). However, as a minimum estimate, these estimators indicated that there are between 7000-10 000 bacterial OTUs in the sediments when clustered at 3% sequence divergence (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…At the 3% clustering level, each of the sediment samples contained twice as many observed OTUs (B4100) as did the water column sample (B1850 OTUs). Chao and ACE estimators tend to underestimate actual richness owing to their extrapolation from small sample sizes (Hong et al, 2006;Quince et al, 2008). However, as a minimum estimate, these estimators indicated that there are between 7000-10 000 bacterial OTUs in the sediments when clustered at 3% sequence divergence (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…An estimate of the total diversity for each sample was calculated using a Bayesian modelling approach as described by Quince et al [33], where the 'posterior distribution' of the taxa area curve is estimated from the known distribution of the data gathered in the sequencing. Three distributions are modelled: Log-normal; Inverse Gaussian; and Sichel, and the Deviance Information Criterion (DIC), as described by Spiegelhalter et al [41] is used to compare the fit from each model.…”
Section: Discussionmentioning
confidence: 99%
“…However, these techniques still only offer a partial view of diversity in a microbial system, and the diversity observed is still typically a function of the number of sequences analysed [32]. These difficulties can be overcome using Bayesian techniques that infer the underlying species abundance curves which in turn can be used to estimate the total diversity of the sample [33,34]. These techniques have the advantage of using a minimum information criteria that allows for the selection of the best fitting model representing the estimated species abundance curves, whilst also providing confidence intervals for these estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, serpentine soils could be good models for metagenomics due to the expected low number of species, in comparison with agricultural or forest soils, and may provide many gene functions for industrial biotechnology applications. It has recently been shown (Quince et al 2008) that an estimate for a soil metagenome would require a tremendous effort, compared with ocean metagenomics. For instance, the international consortium "Terragenome" (http://www.terragenome.org), which is aimed at deciphering at large scale the metagenome of a reference soil, is in fact an ongoing effort which groups scientist from 23 countries and will constitute one of the largest genomic investigations of the next years.…”
Section: Perspectivesmentioning
confidence: 99%